The Education in the Face of Contemporary Challenges of Arabic Language Teaching by Al-Shatiby l Al-Tarbiyyah ‘inda al-Syathibi fi Muwajahati al-Tahaddiyat al-Mu‘asharah fi Ta’limi al-Lughah al-‘Arabiyyah - Nurdianto, Talqis; Hajib, Zainal Abidin (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2023)
Education is part of human’s life and it may be different in its performance and process according to time and place with its challenges. Educational challenges had made the education scientists and teachers of their efforts and innovation to analyze its problem in order to achieve the desired educational goals. This study aimed to reveal the conditions of education in an era in which Al-Shatiby lived with its challenges, problems, the role in addressing it to society and the possibility of applying his thoughts in teaching the Arabic language to non-native speakers with its challenges in our contemporary era. The educational activities of the Arabic language for non-native speakers face its problems and challenges from the other sides. The descriptive method was used to obtain Al-Shatiby's books related to education, the book of approvals as a basic reference in the study and educational references for the Arabic language. Al-Shatiby was well known as a great educator who was concerned with education and mentor of teachers. Besides, he was a jurist, a renewed fundamentalist and an innovative linguist. According to him, worship was the spirit of education and the seeker of knowledge was concerned with decent ethics. The process of education built on four pillars of education should not be separated such as worthwhile science, productive teacher, desired method, and energized learner.